The Determinants of Islamic Banking Capital Structure in Indonesia - Fenty Fauziah; Azhar Latief; Sri Wahyuni Jamal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study aims to analyze and explain the factors that influence capital structure. Capital structure (CS) is measured by Debt to Equity Ratio (DER). Profitability is determined by Return on Assets (ROA) and Net Profit Margin (NPM). Loan to Deposit Ratio (LDR) is used as an indicator of risThis study aims to analyze and explain the factors that influence capital structure. Capital structure (CS) is measured by the Debt to Equity Ratio (DER). Profitability is determined by Return on Assets (ROA) and Net Profit Margin (NPM). Financial to Deposit Ratio (FDR) is used as an indicator of risk. Firm size is projected with Ln TA. The population of this study is all Islamic banks contained in Bank Indonesia, with observation periods starting in 2010 until 2018. The selection of samples in this study is a purposive sampling method. Data analysis and hypothesis testing were carried out by using the Eviews 11 program. The results of the study showed that sharia banking companies, all the independent variables simultaneously had a significant effect on the capital structure. Return on Assets (ROA) and firm size have affected the capital structure. Islamic bank managers in Indonesia choose the capital structure obtained from internal funds and the larger the company, it is necessary to arrange capital structure, to obtain the sustainability of the company in the future.k. Firm size is projected with Ln TA. The population of this research is all Islamic banks contained in Bank Indonesia, with observation periods starting in 2010 until 2017. The selection of samples in this study is purposive sampling method. Data analysis and hypothesis testing were carried out by structural equation model approach using the SPSS program. The results of the study showed that in Islamic sharia companies, all the independent variables simultaneously had a significant effect on the capital structure, partially only the Loan to Deposit Ratio (LDR) variable that did not affect the capital structure, while the other independent variables had a significant temporary effect on conventional Research conducted by the researchers themselves used some of the same variables and using the PLS 3.0 analysis tool there were similar results that only risks did not affect the capital structure. The conclusion of this study is that there is no difference in capital structure in Islamic banking companies and conventional banking companies.